Characteristics of the Microstructure and Mineral Composition of Completely Decomposed Migmatitic Granite. Issue 2 (October 2021) - Yan, Song; Tang, Hua; Wu, Zhenjun; Li, Sitao; Rao, Qizhi
Abstract: Based on the characteristics of special mineral composition, complex internal structure and remarkable water effect of completely decomposed migmatitic granite(CDMG), the mineral composition distribution was obtained by X-ray powder diffraction (XRD), and the microstructure of CDMG with different water content was studied by using scanning electron microscope(SEM). The following new progress was made: The mineral composition of the rock samples is mainly quartz, feldspar, montmorillonite, illite and kaolinite. The microstructure of the sample is composed of coarse-grained quartz and feldspar as the framework, and laminated and fragmental clay minerals as the filling materials, forming a relatively dense framework filling structure. Through statistical analysis of the particle morphology and pore distribution data of CDMG samples, it is found that with the increase of moisture content, the filling structure changes from dense to loose. Because of the swelling potential induced by water absorption of hydrophilic clay minerals, and the uneven distribution of clay minerals such as montmorillonite, the filling materials are not uniformly expanded, which eventually leads to the destruction of the original filling structure and the decrease of the density.